(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: This article explores the life and literary contributions of Jonathan Swift, focusing on his masterpiece, "Gulliver's Travels." Swift's upbringing in Ireland and his experiences as a clergyman and political commentator influenced his satirical approach to critiquing 18th-century European society. Through the adventures of Lemuel Gulliver, Swift employs satire to expose human follies and societal shortcomings, making "Gulliver's Travels" a timeless masterpiece that continues to resonate with readers. The article discusses Swift's literary techniques, themes, and enduring legacy as one of the greatest satirists in English literature.